Behavior of Shelter Animals - McGuire, Betty (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book has resulted from collaborative interactions between academic institutions and animal shelters. It contains a collection of eleven papers (one review and ten research articles) on the behavior of dogs and cats in animal shelters, which can be very challenging environments. The papers focus on stress and behaviors associated with stress; the effectiveness of shelter enrichment programs in reducing stress; the usefulness of shelter behavioral evaluations in predicting behavior and assessing adoptability; and interactions between humans and companion animals. The aim of this book is to provide information that will inform shelter programs and policies, and thereby improve the welfare of shelter animals.